Comparative study of soil fertility status of cold desert Ladakh region before and after cloudburst - ACHARYA, S; SINGH, N; MAURYA, S B; SRIVASTAVA, R B (The Indian Journal of Agricultural Sciences, 2014)
Present study was undertaken to determine loss of soil organic carbon, major and micronutrient status of cold desert Ladakh region as a result of unprecedented cloudburst in August 2010. Heavy rainfall (250 mm) within an hour leading to flash floods resulted in severe loss of standing crops spreading over 1400 ha of agriculture land besides destruction of human, animal lives, infrastructures. In most of the affected areas, top fertile soil completely washed away resulting in severe depletion of various major and micro nutrients essential for good soil health. Soil pH was recorded 8.66 and organic carbon severely depleted from 1.09% to only 0.24% making the soil very loose and poor in WHC. N, P and K (115.4, 1.0 and 103.4 kg/ha respectively) and micronutrient contents were also severelyreduced as compared to original soil. These losses have severe long-term effects on crop productivity and economy of the region. Some ameliorative measures have also been mentioned for improving soil health and sustainable crop production.